The effect of exercises using tennis balls and the helping tools in some basic skills for Futsal women players - Malik, Faris Sami Yousif; Ibrahim, Samer Saad; Asleawa, Wesam Najeeb; Mahdi, Ali Salih (International Journal of Psychosocial Rehabilitation, 2020)
It was for tools to help the training of tennis balls positive impact in raising the level of basic skills (handling, suppressions, scoring). It is advised to increase motivation and suspense among the experimental group players while carrying out their exercises. The exercises used for the experimental group, although difficult, further improved the neuromuscular compatibility of the players. The reliance on the speed of implementation of exercises before the correct performance of skills increased the level of skills. Reliance on prepared exercises used in research to develop the basic skills of female gymnasts. It is advised to Use tennis balls and balls of different weights and sizes in order to develop the basic skills of the players. Diversifying training aids, tools and training methods during the training units. There should be Interest in women’s football, especially age groups, by clubs and the Iraqi Football Association.